Preparation method of near-infrared photothermal antibacterial hydrogel
By grafting the sodium hyaluronate and dopamine, and combining with chitosan, β-glycerol phosphate and collagen, a near-infrared photothermal antibacterial hydrogel was prepared, which solved the problem of the degradation of the performance of existing photothermal materials after long-term use, and achieved efficient and stable antibacterial effect.
Patent Information
- Application Number
- CN202510062112.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
AI Technical Summary
After long-term use or multiple cycles, existing photothermal materials have decreased performance, insufficient stability and circulation stability, and cannot effectively inhibit bacterial growth, limiting their application in wound healing.
By grafting modification of sodium hyaluronic acid-grafted polydopamine (PDA-HA), hyaluronic acid-grafted polydopamine (PDA-HA), and combined with chitosan, β-glycerol phosphate and collagen, a near-infrared photothermal antibacterial hydrogel was prepared. The hydrogel can quickly heat up under near-infrared light irradiation and effectively inhibit bacteria.
After long-term use or multiple cycles, the hydrogel has good performance, excellent stability and circulation stability, which can significantly inhibit bacterial growth and is suitable for the treatment of wound healing and other bacterial infections.
Smart Images

Figure CN119842099A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials and relates to a method for preparing a near-infrared photothermal antibacterial hydrogel. Background Art
[0002] Bacterial infection is a serious problem in medical and daily life, especially in the process of wound healing. In clinical practice, surgical debridement is usually performed to remove necrotic tissue, and traditional dressings such as gauze, bandages and cotton balls are used to treat wounds. However, these traditional care methods have some defects. For example, surgical debridement may cause additional damage and pain to patients; and although traditional dressings such as gauze, bandages and cotton balls can provide a certain physical barrier for wounds, their limited absorption capacity, lack of antibacterial properties and easy adhesion to wounds limit their application range. Therefore, it is particularly important to develop new antibacterial materials and methods.
[0003] In the field of biomedical materials, near-infrared photothermal antibacterial hydrogels have attracted much attention due to their unique photothermal effect. Near-infrared light (NIR) has good tissue penetration ability, is harmless to human tissue, can be effectively absorbed by specific materials and converted into heat energy, effectively inhibiting bacterial growth and promoting wound healing. Existing photothermal materials are limited by their performance degradation after long-term use or multiple cycles, and their lack of stability and cyclic stability. This has prompted researchers to develop a hydrogel dressing with an innovative antibacterial effect for wound antibacterial and healing. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a near-infrared photothermal antibacterial hydrogel in view of the above-mentioned problems existing in the prior art. The technical problem to be solved by the present invention is to prepare an antibacterial hydrogel with good performance and excellent cyclic stability.
[0005] The purpose of the present invention can be achieved by the following technical scheme: A method for preparing a near-infrared photothermal antibacterial hydrogel, characterized in that it comprises the following steps:
[0006] (1) Dissolve 1g sodium hyaluronate in 100mL deionized water to prepare a hyaluronic acid aqueous solution with a mass fraction of 1wt%. Add 1.50g 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 0.91g N-hydroxysuccinimide (NHS) to the hyaluronic acid aqueous solution and stir thoroughly for 2h. Add 1.42g dopamine (DA) at 600r / min and react for 12h, add ammonia water to adjust the pH to 8-9, and stir for 24h in the dark. Wash with deionized water and centrifuge for 3 times, pour into a glass dish, and dry at 60℃ for 15h to obtain hyaluronic acid grafted polydopamine (PDA-HA).
[0007] (2) Dissolve chitosan powder in 0.1 mol / L acetic acid solution to prepare a 1.5% to 3% (W / V) chitosan solution. Dissolve β-sodium glycerophosphate powder in triple distilled water to prepare a 40% to 50% (W / W) solution. Add 1.5 times the volume of triple distilled water to collagen under ice bath, add to 0.1 mol / L NaOH solution, adjust the pH to 7.0 to 7.2, stir well, and prepare a collagen solution.
[0008] (3) The chitosan solution and the β-sodium glycerophosphate solution are mixed in an ice bath at a volume ratio of 4:1 to 7:1 to prepare a chitosan / sodium glycerophosphate solution with a pH value of 7.0 to 7.2.
[0009] (4) The prepared chitosan / sodium glycerophosphate solution and collagen solution are mixed in an ice bath at a volume ratio of 1:10 to 10:1 to prepare a chitosan / sodium glycerophosphate / collagen hydrogel.
[0010] (5) PDA-HA powder is mixed with chitosan / sodium glycerophosphate / collagen hydrogel at a mass ratio of 0.01 to 0.03:20, and the copolymer of the four substances is obtained after sufficient stirring. The thermosensitive hydrogel is simple and convenient to use and has a significant antibacterial effect.
[0011] Furthermore, the molecular weight (MW) of the sodium hyaluronate is 200-400 kDa, and the molecular weight (MW) of the dopamine is 189.64.
[0012] Furthermore, the hyaluronic acid solution is prepared at room temperature and magnetically stirred at 500-800 r / min for 30-60 min to make the solution evenly dispersed.
[0013] Furthermore, the mixing time of the hyaluronic acid solution, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide is 2 hours, and the rotation speed is 600 r / min.
[0014] Furthermore, in step (1), the rotation speed of the water washing centrifuge is 12000 rpm, the centrifugation time is about 10 min, and the temperature is lower than 30°C.
[0015] Furthermore, the particle size of the hyaluronic acid grafted modified polydopamine nanoparticles is 400-600nm.
[0016] Furthermore, the chitosan solution and the β-sodium glycerophosphate solution are mixed and stirred for 30-60 minutes at a rotation speed of 300-400 rpm.
[0017] Furthermore, the chitosan / sodium glycerophosphate solution and the collagen solution are mixed and stirred for 10-20 minutes at a rotation speed of 300-400 rpm.
[0018] Furthermore, the mixing time of the PDA-HA powder and the chitosan / sodium glycerophosphate / collagen hydrogel is 30-60 minutes, and the rotation speed is 300-400 rpm.
[0019] Polydopamine (PDA) nanoparticles have become a potential photothermal material due to their excellent photothermal conversion performance, unique antibacterial ability and simple green preparation process. A large number of studies have shown that PDA can quickly convert light energy into heat energy under near-infrared light irradiation. In addition, the surface of PDA is rich in catechol groups, which enable it to interact with a variety of biomolecules. Hyaluronic acid is grafted on the surface of polydopamine nanoparticles to improve the stability of polydopamine nanoparticles (PDANPs). The present invention prepares a new type of near-infrared photothermal antibacterial hydrogel by encapsulating PDA-HA in a hydrogel. It can quickly heat up to an effective antibacterial temperature under near-infrared light irradiation and can be used to treat various types of bacterial infections, including but not limited to skin infections, burns, infected wounds and surgical site infections.
[0020] The beneficial effects of the present invention are:
[0021] (1) The photothermal material provided by the present invention has good performance, excellent stability and cycle stability after long-term use or multiple cycles.
[0022] (2) The photothermal material provided by the present invention has good biocompatibility, is non-toxic to cells, and has good biosafety.
[0023] (3) The photothermal material preparation method provided by the present invention is simple and easy, the raw materials are easily available, and it is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a physical picture of the hydrogel dressing (CSCP) for wound healing prepared in Example 1.
[0025] Figure 2 This is the Fourier transform infrared spectrum of PDA-HA prepared in Example 2.
[0026] Figure 3 This is a near-infrared response graph of the hydrogel dressing for wound healing (CSCP) prepared in Example 3 changing over time under near-infrared light irradiation.
[0027] Figure 4 This is a diagram showing the antibacterial effect of the hydrogel dressing for wound healing prepared in Example 4 on Staphylococcus aureus and Escherichia coli (plate count method).
[0028] Figure 5This is a diagram showing the effect of the hydrogel dressing for wound healing (CSCP) prepared in Example 5 on wound healing in rats. DETAILED DESCRIPTION
[0029] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0030] Example 1: A method for preparing a near-infrared photothermal antibacterial hydrogel, comprising the following steps:
[0031] (1) At room temperature, dissolve 1g of sodium hyaluronate with a molecular weight (MW) of 200-400kDa in 100mL of deionized water to prepare a hyaluronic acid aqueous solution with a mass fraction of 1wt%. Add 1.50g of EDC and 0.91g of NHS to the hyaluronic acid aqueous solution and stir thoroughly for 2h. Add 1.42g of dopamine with a molecular weight (MW) of 189.64 at a speed of 600r / min and react for 12h, add ammonia water to adjust the pH to 8-9, and stir for 24h in the dark. Wash with deionized water and centrifuge 3 times, pour into a polypropylene lid, and dry at 60℃ for 15h to obtain PDA-HA.
[0032] (2) Dissolve chitosan powder in 0.1 mol / L acetic acid solution to prepare a 1.5% (W / V) chitosan solution. Dissolve β-sodium glycerophosphate powder in triple distilled water to prepare a 40% (W / W) solution. Add 1.5 times the volume of triple distilled water to collagen under ice bath, add the solution to 0.1 mol / L NaOH solution, adjust the pH to 7.0, and stir thoroughly to prepare a collagen solution.
[0033] (3) The chitosan solution and the β-sodium glycerophosphate solution were mixed in an ice bath at a volume ratio of 4:1 to prepare a chitosan / sodium glycerophosphate solution with a pH value of 7.0.
[0034] (4) The prepared chitosan / sodium glycerophosphate solution and collagen solution were mixed in an ice bath at a volume ratio of 5:5 to prepare a chitosan / sodium glycerophosphate / collagen hydrogel.
[0035] (5) PDA-HA powder was mixed with chitosan / sodium glycerophosphate / collagen hydrogel at a mass ratio of 0.02:20, and the copolymer of the four substances was obtained after sufficient stirring. The hydrogel is simple and convenient to use and has a significant antibacterial effect.
[0036] The prepared hydrogel dressing for wound healing (CSCP) is shown in FIG. Figure 1 shown.
[0037] Example 2: A method for preparing a near-infrared photothermal antibacterial hydrogel, comprising the following steps:
[0038] (1) At room temperature, dissolve 1g of sodium hyaluronate with a molecular weight (MW) of 200-400kDa in 100mL of deionized water to prepare a hyaluronic acid aqueous solution with a mass fraction of 1wt%. Add 1.50g of EDC and 0.91g of NHS to the hyaluronic acid aqueous solution and stir thoroughly for 2h. Add 1.42g of dopamine with a molecular weight (MW) of 189.64 at a speed of 600r / min and react for 12h, add ammonia water to adjust the pH to 8-9, and stir for 24h in the dark. Wash with deionized water and centrifuge for 3 times, pour into a polypropylene lid, and dry at 60℃ for 15h to obtain PDA-HA.
[0039] (2) Dissolve chitosan powder in 0.1 mol / L acetic acid solution to prepare a 2% (W / V) chitosan solution. Dissolve β-sodium glycerophosphate powder in triple distilled water to prepare a 45% (W / W) solution. Add 1.5 times the volume of triple distilled water to collagen under ice bath, add the solution to 0.1 mol / L NaOH solution, adjust the pH to 7.0, and stir thoroughly to prepare a collagen solution.
[0040] (3) The chitosan solution and the β-sodium glycerophosphate solution were mixed in an ice bath at a volume ratio of 5:1 to prepare a chitosan / sodium glycerophosphate solution with a pH value of 7.0.
[0041] (4) The prepared chitosan / sodium glycerophosphate solution and collagen solution were mixed in an ice bath at a volume ratio of 6:4 to prepare a chitosan / sodium glycerophosphate / collagen hydrogel.
[0042] (5) PDA-HA powder was mixed with chitosan / sodium glycerophosphate / collagen hydrogel at a mass ratio of 0.02:20, and the copolymer of the four substances was obtained after sufficient stirring. The hydrogel is simple and convenient to use and has a significant antibacterial effect.
[0043] FT-IR spectra of DA, HA, PDA and PDA-HA are shown in Figure 2. Figure 2 As shown. The absorption peak of pure HA appears at 1607 cm -1 , which represents the asymmetric stretching peak of the carboxyl group. DA has multiple characteristic absorption peaks in the infrared spectrum, at 3500-3200 cm -1 The broad absorption peaks near 1590 cm-1 correspond to the stretching vibrations of hydroxyl (-OH) and amino (-NH2). -1 The peak at 1504 cm is related to the C=C stretching vibration of the indole group of PDA. -1 There is a characteristic absorption peak at 1680-1630cm, which may be the formation of amide bond. Since HA itself contains amide groups and HA is grafted onto the amino group of PDA by amide condensation, the amide bond is the key to examine whether HA grafting is successful. -1The characteristic peak of the amide band at 1570-1510 cm -1 There is an obvious amide second band characteristic peak at 1210cm -1 and 1050cm -1 The absorption peaks appearing at are the OH deformation vibration peak of secondary alcohol and the CO stretching vibration peak of saturated secondary alcohol. Based on this, the appearance of the above HA-specific absorption peaks proves that HA is introduced on the PDA surface.
[0044] Example 3: A method for preparing a near-infrared photothermal antibacterial hydrogel, comprising the following steps:
[0045] (1) At room temperature, dissolve 1g of sodium hyaluronate with a molecular weight (MW) of 200-400kDa in 100mL of deionized water to prepare a hyaluronic acid aqueous solution with a mass fraction of 1wt%. Add 1.50g of EDC and 0.91g of NHS to the hyaluronic acid aqueous solution and stir thoroughly for 2h. Add 1.42g of dopamine with a molecular weight (MW) of 189.64 at a speed of 600r / min and react for 12h, add ammonia water to adjust the pH to 8-9, and stir for 24h in the dark. Wash with deionized water and centrifuge 3 times, pour into a polypropylene lid, and dry at 60℃ for 15h to obtain PDA-HA.
[0046] (2) Dissolve chitosan powder in 0.1 mol / L acetic acid solution to prepare a 2.5% (W / V) chitosan solution. Dissolve β-sodium glycerophosphate powder in triple distilled water to prepare a 45% (W / W) solution. Add 1.5 times the volume of triple distilled water to collagen under ice bath, add the solution to 0.1 mol / L NaOH solution, adjust the pH to 7.1, and stir thoroughly to prepare a collagen solution.
[0047] (3) The chitosan solution and the β-sodium glycerophosphate solution were mixed in an ice bath at a volume ratio of 6:1 to prepare a chitosan / sodium glycerophosphate solution with a pH value of 7.1.
[0048] (4) The prepared chitosan / sodium glycerophosphate solution and collagen solution were mixed in an ice bath at a volume ratio of 5:5 to prepare a chitosan / sodium glycerophosphate / collagen hydrogel.
[0049] (5) PDA-HA powder was mixed with chitosan / sodium glycerophosphate / collagen hydrogel at a mass ratio of 0.03:20, and the copolymer of the four substances was obtained after sufficient stirring. The hydrogel was simple and convenient to use and had a significant antibacterial effect.
[0050] Figure 3This is a near-infrared response diagram of the hydrogel dressing for wound healing (CSCP) prepared in Example 3 under near-infrared light irradiation. The temperature of the CSCP hydrogel gradually increases with the near-infrared light irradiation time. The CSCP hydrogel at 2 W / cm 2 After 5 minutes of near-infrared light irradiation, the temperature can reach 45.3℃.
[0051] Example 4: A method for preparing a near-infrared photothermal antibacterial hydrogel, comprising the following steps:
[0052] (1) At room temperature, dissolve 1g of sodium hyaluronate with a molecular weight (MW) of 200-400kDa in 100mL of deionized water to prepare a hyaluronic acid aqueous solution with a mass fraction of 1wt%. Add 1.50g of EDC and 0.91g of NHS to the hyaluronic acid aqueous solution and stir thoroughly for 2h. Add 1.42g of dopamine with a molecular weight (MW) of 189.64 at a speed of 600r / min and react for 12h, add ammonia water to adjust the pH to 8-9, and stir for 24h in the dark. Wash with deionized water and centrifuge 3 times, pour into a polypropylene lid, and dry at 60℃ for 15h to obtain PDA-HA.
[0053] (2) Dissolve chitosan powder in 0.1 mol / L acetic acid solution to prepare a 3% (W / V) chitosan solution. Dissolve β-sodium glycerophosphate powder in triple distilled water to prepare a 50% (W / W) solution. Add 1.5 times the volume of triple distilled water to collagen under ice bath, add the solution to 0.1 mol / L NaOH solution, adjust the pH to 7.0, and stir thoroughly to prepare a collagen solution.
[0054] (3) The chitosan solution and the β-sodium glycerophosphate solution were mixed in an ice bath at a volume ratio of 4:1 to prepare a chitosan / sodium glycerophosphate solution with a pH value of 7.0.
[0055] (4) The prepared chitosan / sodium glycerophosphate solution and collagen solution were mixed in an ice bath at a volume ratio of 4:6 to prepare a chitosan / sodium glycerophosphate / collagen hydrogel.
[0056] (5) PDA-HA powder was mixed with chitosan / sodium glycerophosphate / collagen hydrogel at a mass ratio of 0.02:20, and the copolymer of the four substances was obtained after sufficient stirring. The hydrogel is simple and convenient to use and has a significant antibacterial effect.
[0057] Figure 4 The antibacterial effect of the hydrogel dressing for wound healing prepared in Example 4 on Staphylococcus aureus and Escherichia coli (plate count method). This study used S. aureus and E. coli as representative pathogenic bacteria models, and the dilution plate method was used to evaluate the antibacterial properties of each group of samples. Figure 4As shown in the figure, under dark conditions, a large number of S. aureus and E. coli can be seen on the agar plate of the saline group, while the colony density in the culture medium corresponding to the CSC / Dark group and the CSCP / Dark group is lower than that of the PBS / Dark group. After the introduction of NIR light, the antibacterial performance of the PBS / NIR group did not improve significantly, and a large number of colonies still existed on the surface. It is worth noting that bacteria still grew in the CSC group under NIR light irradiation, while no bacteria grew in the CSCP group under NIR light irradiation, showing a significant antibacterial effect with an antibacterial rate of 100%. This is because under NIR irradiation, PDA-HA can efficiently absorb the energy of near-infrared light and convert it into heat energy, causing the temperature of the surrounding environment to rise rapidly, thereby killing bacteria.
[0058] Example 5: A method for preparing a near-infrared photothermal antibacterial hydrogel, comprising the following steps:
[0059] (1) At room temperature, dissolve 1g of sodium hyaluronate with a molecular weight (MW) of 200-400kDa in 100mL of deionized water to prepare a hyaluronic acid aqueous solution with a mass fraction of 1wt%. Add 1.50g of EDC and 0.91g of NHS to the hyaluronic acid aqueous solution and stir thoroughly for 2h. Add 1.42g of dopamine with a molecular weight (MW) of 189.64 at a speed of 600r / min and react for 12h, add ammonia water to adjust the pH to 8-9, and stir for 24h in the dark. Wash with deionized water and centrifuge 3 times, pour into a polypropylene lid, and dry at 60℃ for 15h to obtain PDA-HA.
[0060] (2) Dissolve chitosan powder in 0.1 mol / L acetic acid solution to prepare a 3% (W / V) chitosan solution. Dissolve β-sodium glycerophosphate powder in triple distilled water to prepare a 45% (W / W) solution. Add 1.5 times the volume of triple distilled water to collagen under ice bath, add the solution to 0.1 mol / L NaOH solution, adjust the pH to 7.2, and stir thoroughly to prepare a collagen solution.
[0061] (3) The chitosan solution and the β-sodium glycerophosphate solution were mixed in an ice bath at a volume ratio of 7:1 to prepare a chitosan / sodium glycerophosphate solution with a pH value of 7.0.
[0062] (4) The prepared chitosan / sodium glycerophosphate solution and collagen solution were mixed in an ice bath at a volume ratio of 3:7 to prepare a chitosan / sodium glycerophosphate / collagen hydrogel.
[0063] (5) PDA-HA powder was mixed with chitosan / sodium glycerophosphate / collagen hydrogel at a mass ratio of 0.02:20 and stirred thoroughly to obtain a copolymer of the four substances. The hydrogel is simple and convenient to use and has a significant antibacterial effect. Its effect on wound healing in rats is shown in Figure 2. Figure 5 shown.
[0064] Example 6: A method for preparing a near-infrared photothermal antibacterial hydrogel, comprising the following steps:
[0065] (1) At room temperature, dissolve 1g of sodium hyaluronate with a molecular weight (MW) of 200-400kDa in 100mL of deionized water to prepare a hyaluronic acid aqueous solution with a mass fraction of 1wt%. Add 1.50g of EDC and 0.91g of NHS to the hyaluronic acid aqueous solution and stir thoroughly for 2h. Add 1.42g of dopamine with a molecular weight (MW) of 189.64 at a speed of 600r / min and react for 12h, add ammonia water to adjust the pH to 8-9, and stir for 24h in the dark. Wash with deionized water and centrifuge 3 times, pour into a polypropylene lid, and dry at 60℃ for 15h to obtain PDA-HA.
[0066] (2) Dissolve chitosan powder in 0.1 mol / L acetic acid solution to prepare a 2.5% (W / V) chitosan solution. Dissolve β-sodium glycerophosphate powder in triple distilled water to prepare a 50% (W / W) solution. Add 1.5 times the volume of triple distilled water to collagen under ice bath, add the solution to 0.1 mol / L NaOH solution, adjust the pH to 7.0, and stir thoroughly to prepare a collagen solution.
[0067] (3) The chitosan solution and the β-sodium glycerophosphate solution were mixed in an ice bath at a volume ratio of 5:1 to prepare a chitosan / sodium glycerophosphate solution with a pH value of 7.0.
[0068] (4) The prepared chitosan / sodium glycerophosphate solution and collagen solution were mixed in an ice bath at a volume ratio of 8:2 to prepare a chitosan / sodium glycerophosphate / collagen hydrogel.
[0069] (5) PDA-HA powder was mixed with chitosan / sodium glycerophosphate / collagen hydrogel at a mass ratio of 0.03:20, and the copolymer of the four substances was obtained after sufficient stirring. The hydrogel was simple and convenient to use and had a significant antibacterial effect.
[0070] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A method for preparing a near-infrared photothermal antibacterial hydrogel, characterized in that: The following steps are included. (1) Dissolve 1 g of sodium hyaluronate in 100 mL of deionized water to prepare a hyaluronic acid aqueous solution with a mass fraction of 1 wt%; add 1.50 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.91 g of N-hydroxysuccinimide to the hyaluronic acid aqueous solution and stir thoroughly for 2 h; then add 1.42 g of dopamine at a speed of 600 r / min and react for 12 h, add ammonia water to adjust the pH to 8-9, and stir in the dark for 24 h; Wash with deionized water and centrifuge for 3 times, pour into a glass dish, and dry at 60°C for 15h to 30h to obtain hyaluronic acid-grafted polydopamine; (2) dissolving chitosan powder in 0.1 mol / L acetic acid solution to prepare a 1.5% to 3% (W / V) chitosan solution; dissolving β-sodium glycerophosphate powder in triple distilled water to prepare a 40% to 50% (W / W) β-sodium glycerophosphate solution; adding 1.5 times the volume of triple distilled water to collagen in an ice bath, adding to a 0.1 mol / L NaOH solution, adjusting the pH value to 7.0 to 7.2, and stirring thoroughly to prepare a collagen solution; (3) mixing the chitosan solution and the sodium β-glycerophosphate solution in a volume ratio of 4:1 to 7:1 in an ice bath to prepare a chitosan / sodium glycerophosphate solution with a pH value of 7.0 to 7.2; (4) mixing the prepared chitosan / sodium glycerophosphate solution and collagen solution in a volume ratio of 1:10 to 10:1 under ice bath to prepare chitosan / sodium glycerophosphate / collagen hydrogel; (5) The hyaluronic acid grafted polydopamine powder is mixed with chitosan / sodium glycerophosphate / collagen hydrogel at a mass ratio of 0.01 to 0.03:20, and the copolymer of the four substances is obtained after sufficient stirring, that is, the near-infrared photothermal antibacterial hydrogel is obtained.
2. The method according to claim 1, characterized in that In step (1), the molecular weight (MW) of sodium hyaluronate is 200-400 kDa, and the molecular weight (MW) of dopamine is 189.
64.
3. The method according to claim 1, characterized in that The preparation conditions of the hyaluronic acid solution in step (1) are room temperature and magnetic stirring at 500-800 r / min for 30-60 min to make the solution evenly dispersed.
4. The method according to claim 1, characterized in that: In step (1), the rotation speed of the water washing centrifuge is 12000 rpm, the centrifugation time is about 10 min, and the temperature is below 30°C.
5. The method according to claim 1, characterized in that The particle size of the hyaluronic acid grafted modified polydopamine nanoparticles is 400-600nm.
6. The method according to claim 1, characterized in that The chitosan solution and the β-sodium glycerophosphate solution are mixed and stirred for 30-60 minutes at a rotation speed of 300-400 rpm.
7. The method according to claim 1, characterized in that The chitosan / sodium glycerophosphate solution and the collagen solution are mixed and stirred for 10-20 minutes at a rotation speed of 300-400 rpm.
8. The method according to claim 1, characterized in that The hyaluronic acid grafted polydopamine powder and chitosan / sodium glycerophosphate / collagen hydrogel are mixed and stirred for 30-60 minutes at a rotation speed of 300-400 rpm.